Infertility in Fabry’s Disease: role of hypoxia and inflammation in determining testicular damage - Sansone, Luigi; Barreca, Federica; Belli, Manuel; Aventaggiato, Michele; Russo, Andrea; Perrone, Giulietta A.; Russo, Matteo A.; Tafani, Marco; Frustaci, Andrea (Frontiers in Endocrinology, 2024)
Introduction: Fabry's disease (FD) is a genetic X-linked systemic and progressive rare disease characterized by the accumulation of globotriaosylceramide (GB3) into the lysosomes of many tissues. FD is due to loss-of-function mutations of α-galactosidase, a key-enzyme for lysosomal catabolism of glycosphingolipids, which accumulate as glycolipid bodies (GB). In homozygous males the progressive deposition of GB3 into the cells leads to clinical symptoms in CNS, skin, kidney, etc. In testis GB accumulation causes infertility and alterations of spermatogenesis. However, the precise damaging mechanism is still unknown. Our hypothesis is that GB accumulation reduces blood vessel lumen and increases the distance of vessels from both stromal cells and seminiferous parenchyma; this, in turn, impairs oxygen and nutrients diffusion leading to subcellular degradation of seminiferous epithelium and sterility. Methods: To test this hypothesis, we have studied a 42-year-old patient presenting a severe FD and infertility, with reduced number of spermatozoa, but preserved sexual activity. Testicular biopsies were analyzed by optical (OM) and transmission electron microscopy (TEM). Activation and cellular localization of HIF-1α and NFκB was analyzed by immunofluorescence (IF) and RT-PCR on homogeneous tissue fractions after laser capture microdissection (LCMD). Results: OM and TEM showed that GB were abundant in vessel wall cells and in interstitial cells. By contrast, GB were absent in seminiferous epithelium, Sertoli's and Leydig's cells. However, seminiferous tubular epithelium and Sertoli's cells showed reduced diameter, thickening of basement membrane and tunica propria, and swollen or degenerated spermatogonia. IF showed an accumulation of HIF-1α in stromal cells but not in seminiferous tubules. On the contrary, NFκB fluorescence was evident in tubules, but very low in interstitial cells. Finally, RT-PCR analysis on LCMD fractions showed the expression of pro-inflammatory genes connected to the HIF-1α/NFκB inflammatory-like pathway.Our study demonstrates that infertility in FD may be caused by reduced oxygen and nutrients due to GB accumulation in blood vessels cells. Reduced oxygen and nutrients alter HIF-1α/NFκB expression and localization while activating HIF-1α/NFκB driven-inflammation-like response damaging seminiferous tubular epithelium and Sertoli's cells.